Does Tourism Really Matter for Economic Growth? Evidence from Nepal - Paudyal, Shoorabeer (NRB Economic Review, 2012)
Tourism seems to be widely recognized as the one among a few sectors in Nepal which can be an engine of economic growth. However, there are few empirical studies about Nepalese tourism. This paper, thus, attempts to examine the impact of tourism and other related macroeconomic variables on the economic growth of Nepal by deriving tourism income multiplier from the Keynesian macroeconomic model. The three stage least square and seemingly unrelated regressions are the techniques employed for estimating the value of multiplier. The estimated value of multiplier based on regression results over thirty six year period from 1975 to 2010 is estimated at 1.21. In addition, Granger causality tests are used to confirm the direction of the impact of one variable on another variable, which reveals that there exists bi-directional impact in the case of tourism receipts and GDP.  In addition, tourism receipts are found to have bi-directional relationship with some other variables such as GNI, exports, private consumption, imports and so on. Thus, tourism multiplier and the Granger causality tests show that tourism is important component for economic growth in Nepal.